Intraday price formation and volatility in the European Union emissions trading scheme: an introductory analysis - Waldemar Rotfuß (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2009)
This paper presents an introductory analysis of price formation and volatility in the European Union Emissions Trading Scheme using highfrequency data. The results show that there are several anomalies both in the EUA spot and EUA futures market. First, price formation seems to take place on price sets that are coarser than those offered by the exchanges. Second, price formation in the EUA spot market (BlueNext) may be strongly affected by the price formation in the EUA futures market (ICE Futures). The typical U-shaped pattern of intraday volatility, that is often observed in organized financial markets, is partly present in the EUA futures market. Similar to other classical financial markets, realized volatility estimates of daily EUA volatility seem to have a long-memory property.
Keywords: D43; G13; Q59; 330; EUA; EU ETS; Intraday Price Formation; Realized Volatility; Emissionshandel; Preis; Volatilität; Zeit; EU-Staaten